Visualisasi Mental untuk Konsentrasi Pemain Basket - Marpaung, Deni Rahman; Rangkuti, Salman Rasyid; Batubara, Muhammad Sevat Azra; Maulana, Gilang; Sitorus, Ronaldo Paulus; Sinaga, Febri Doli Maruli (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to determine the mental visualization and concentration of basketball players. This visualization affects the concentration of basketball players at SMA N 2 Medan. Physical education is a compulsory subject taught in Senior High Schools (SMA). In physical education learning activities, the most important thing related to the occurrence of an effective learning process in students is the teacher's ability to combine various learning conditions into learning activities, combining these learning conditions in the form of a teaching method. From the results of interviews conducted by researchers, several physical education teachers at the school stated that students are usually slow to master the basic techniques of basketball Lay Up so that the Minimum Passing Criteria (KKM) are difficult to achieve. Based on this problem, thoughts and desires arose to find alternative teaching models to convey basic basketball Lay Up techniques. In this case, an alternative was proposed by providing mental imagery training to students. Mental imagery is a person's ability to build a motion picture or skill in the mind or in the mind. Researchers want to know the effect of mental imagery training on student learning outcomes in mastering basic basketball Lay Up techniques in physical education learning. The population in this study was all students of class XI SMA Negeri 2 Medan. From this study it can be concluded that the use of mental imagery training has a significant effect on students' ability to master basic basketball dribbling techniques.